Analisis Pengujian Otomatisasi pada Situs Web E-Commerce dan Tanggapan Pengguna - Mutiara Ayu Rizky; Antoni Wibowo (Society, 2025)
This study compares two automation testing tools, Robot Framework and Cypress, applied to e-commerce websites. The testing procedure is based on predefined test case flows utilizing the Black Box Testing method, which focuses exclusively on functional validation according to requirement specifications, without reference to backend systems or source code. The research aims to evaluate the efficiency and effectiveness of both tools in executing identical test scenarios and to assess user responses concerning website access speed. Robot Framework, recognized for its keyword-driven testing approach, is compared with Cypress, a JavaScript-based end-to-end testing framework. The findings indicate that Cypress outperforms Robot Framework, particularly regarding execution speed and automated report generation. Cypress’s modern architecture and real-time interaction capabilities contribute to faster and more stable test execution. Conversely, while Robot Framework offers significant flexibility and extensibility, its performance is comparatively slower in this context. User feedback suggests that the Bhinneka, Gramedia, and Uniqlo websites are generally responsive and user-friendly; however, Uniqlo is notably preferred due to its accurate stock information and efficient delivery services.